CHIZMACHILIK DARSLARIDA IJODIY IZLANISHLAR VA O’YINLI TEXNALOGYALARDAN FOYDALANISH (Charxpalak metodi misolida) - Yakubova, N.O. (SCIENCE and SOCIETY, 2021)
The process of human cognitive activity is based on the problem of the didactic principle of objective regularities in resolving logical cognitive contradictions. The purpose of engineering graphics in the formation of the worldview, spatial perception of the child, as well as modeling and design through drawing lessons is stated.